THE EFFECT OF THE PERCEPTION OF SERVICE QUALITY ON THE DECISION OF PURCHASE IN DAWET JABUNG TRADERS IN PONOROGO - Ardiana, Titin Eka (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
This study aims to find out: to find out whether there is an influence on the perception of Service Quality on Repurchase Decisions on Dawet Jabung Traders in Ponorogo. This study uses a quantitative approach with a sample of all customers who have made purchases at the Dawet Jabung UKM in Mlarak District, Ponorogo Regency. The variable of this study consists of one independent variable, namely the perception of service quality (X1) and one dependent variable, namely the purchasing decision (Y). Data collection is done using indirect questionnaires or techniques. The results of data collection were then analyzed using simple and multiple linear regression analysis techniques with the help of SPSS Version 20. The results showed that: (1) Variable perceptions of service quality in this study were able to explain 9.4% variation in the Dawet Jabung Ponorogo MSME decision. While the remaining 90.6% is explained by variables or aspects outside the model, and (2) From the results of the F test shows that the perception variable service quality is a feasible variable to test the variable repurchase decisions in dawet UMKM Jabung Ponorogo . Keywords : Perception Of Service Quality, Purchasing Decisions